Efficient hydrogenation of CO2 to formic acid over amorphous NiRuB catalysts. Issue 54 (December 2021) - He, Jiehong; Chang, Shaoshuai; Du, Haoran; Jiang, Bo; Yu, Wenzhao; Wang, Zhenwu; Chu, Weiwei; Han, Lanfang; Zhu, Jian; Li, Hexing
Graphical abstract: Highlights: A bimetallic amorphous alloy (NiRuB) was synthesized and exhibited high activity and selectivity to HCOOH in CO2 hydrogenation. The unique amorphous alloy structure promotes the CO2 activation and H2 dissociation due to the electron donation effect of B. Increased electron density in metal due to Ru electronegativity and Ni geometric effect facilitated CO2 insertion into M-H and H atoms migration. Abstract: The hydrogenation of carbon dioxide (CO2 ) to formic acid (FA) has been considered as a promising approach to utilize CO2 and realize carbon-neutral energy supply. Development of efficient heterogeneous catalysts is an interesting yet challenging task. In this work, a reliable amorphous NiRu0.1 B catalyst was presented and displayed a sufficient catalytic activity for the hydrogenation of CO2 into FA. The amorphous structure of catalysts provided abundant dangling bonds and unsaturated atoms for enhancement of the reactant gas adsorption. Moreover, the electron-donating effect of B element is crucial for creating active electron-rich metal centres, which is proposed to facilitate the formation of the MH for activating CO2 molecules. Owing to synergistic effect of amorphous structure and electron-donating, amorphous NiRu0.1 B catalysts show a higher activity and stability than that of Ni-B and crystalline Ni-B at low temperature. This work not only exhibits a facile method to prepare amorphous bimetallic catalysts, also demonstrates that amorphous metals are promising heterogeneous catalysts for the hydrogenation of CO2 to FA.